Energy policy and conservation planning in Sweden: a longitudinal evaluation. Issue 4 (12th May 2020) - Legnér, Mattias; Leijonhufvud, Gustaf; Tunefalk, Martin
Abstract : Purpose: Sweden, like other countries, has set ambitious national targets for both energy efficiency and conservation of heritage values in the built environment. However, how these policies are implemented on a local level and how they affect each other is not known. This study aims to argue that extensive energy-saving policies can have unintentional impacts not just on the built environment but also on conservation practice. Design/methodology/approach: By using a longitudinal approach, the aim is to investigate the possibilities of conserving the built environment when policies for increased energy efficiency are implemented in existing urban areas. The methodology used is qualitative, applying a combination of study of public records, policy documents, interviews with public officials and ocular investigation of buildings in three areas located in two different municipalities. Findings: The study suggests that extensive refurbishments not only have effects on the character of an area, but in extension, affect how urban planners and local authorities approach the development in the same area. Urban areas affected by extensive retrofits in the past seem to be managed in less detail, leaving existing policy measures on both energy and heritage untapped. Research limitations/implications: This is a study concerning two Swedish municipalities. Furthermore, it is limited to one specific policy measure, energy-saving subsidies provided in the 1970s and 1980s. The generalisability of the findings may, therefore, be limited. Despite this, the findings provide an important indication of the relationship between energy-saving policies in the past and urban planning practice of existing urban areas today, as well as the importance of alignment between policy-making and implementation. Practical implications: Policy instruments for the building stock and the practice of conservation planning have not worked well together. Due to local practice, energy subsidies provided in the 1970s and 1980s still today have a negative effect on both heritage conservation and energy efficiency in existing areas. Social implications: There is a discrepancy between expectations and outcome of policy measures. National decision-makers overestimate the possibilities to control the development on a local level, for both energy efficiency and heritage values. By examining an innovative set of sources, acknowledging long-term effects and entanglements of policies and practice, this study contributes to a better understanding of the complexity of different values in the built environment. Originality/value: By comparing the share of approved applications, as well as completed energy retrofits, this study demonstrates that the effects of the national energy subsidy policy differed significantly between urban areas. Areas with a high degree of approved subsidies also had a high degree of retrofits, suggesting that the policy had intended effects. In these areas, the number of retrofits were also significantly higher than the number of subsidies. This was not the case where energy subsidies were fewer, which indicates that energy retrofits are performative, meaning that they accelerate further retrofits in the same area.